Delays in Diagnosis and Treatment of Bacterial Meningitis in NYC: Retrospective Cohort Analysis. (April 2022) - Torres, Sarah D.; Kim, Carla Y.; Das, Mitashee; Ankam, Jyoti V.; Luche, Nicole; Harmon, Michael; Schorr, Emily M.; Glassberg, Brittany; Morse, Stephen S.; Weiss, Don; Gofshteyn, Jacqueline S.; Yeshokumar, Anusha K.; et al.
Community-acquired bacterial meningitis (CABM) morbidity and mortality remains high in those infected. Rapid diagnosis and treatment is paramount to reducing mortality and improving outcome. This retrospective cohort study aims to assess the time from presentation to diagnosis and treatment of vaccine preventable CABM as well as identify possible factors associated with delays in diagnosis and antibiotic administration. A retrospective chart review was conducted of individuals who presented to Columbia University Irving Medical Center (CUIMC), Children's Hospital of New York (CHONY), Mount Sinai Medical Center, and Weill Cornell Medical Center with BM due to Haemophilus influenzae type B, Streptococcus pneumoniae, and Neisseria meningitidis between January 1, 2012 and December 31, 2017. Diagnosis was delayed by more than 8 hours in 13 patients (36.1%) and 5 individuals (13.9%) had a delay of 4 hours or more from presentation to the administration of antibiotics with appropriate CNS coverage. All of these patients were also initially misdiagnosed at an outpatient clinic, outside hospital, or emergency department. This retrospective study identified febrile and/or viral infections not otherwise specified and otitis media as the most common misdiagnoses underlying delays from presentation to diagnosis and to antibiotic treatment in those with BM.